Pengaruh Latihan Drills For Gamelike Situation dan Drills Under Simplified Conditions terhadap Kemampuan Smash Bola Voli - Sasmita, Khairul; Welis, Wilda; Rifki, Muhamad Sazeli; Rasyid, Willadi; Ockta, Yovhandra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to see the influence of two treatment groups, namely Drills for Game-Like Situation and Drills Under Simplified Conditions, on volleyball smash ability. The results showed that Drills for Game-Like Situation had a significant influence on smash ability. There was an increase in average from pretest 1.8 to posttest 2.4 with a difference of 0.6. Drills for Game-Like Situations and Drills Under Simplified Conditions also significantly affect the smash ability of athletes. The average score of the pretest was 1.8, and the posttest became 2.2 with a difference of 0.4. The increase in smash ability was higher in the drills for gamelike situation training group, which was 33.3%, while Drills Under Simplified Conditions increased by 21.3%. Thus, it can be concluded that Drills for Game-Like Situation is more effective in improving smash ability compared to Drills Under Simplified Conditions. This study provides evidence that Drills for Game-Like Situation exercises can be a better alternative to improve the smash ability of volleyball athletes. In conclusion, the effect of two treatment groups, namely Drills for Game-Like Situation and Drills Under Simplified Conditions, on the volleyball smash ability. Keywords: Drills For Gamelike Situation, Drills Under Simplified Conditions, Smash Ability Volly Ball